Factors Associated with Severe Dehydrating Diarrhoea in the Rural Western Cape, South Africa. (5th February 2018) - van der Westhuizen, Frans P; Slogrove, Amy L; Kunneke, H Marlize; Kruger, Mariana
Abstract: Background: Acute diarrhoea (AD) remains a leading cause of childhood death. We evaluated whether delayed healthcare seeking was associated with severe dehydration in rural South Africa. Methods: In a prospective cohort study of children with AD admitted to a secondary-level hospital, data were collected through structured caregiver interviews and hospital record review. The primary outcome was severe dehydration/death, and the primary determinant was delay >12 h between AD symptom onset and healthcare facility presentation. Results: Total 68% (71 of 104) of children experienced a delay, and 51% (54 of 104) had severe dehydration with no in-hospital deaths. There was no difference in children with (35 of 71) or without (19 of 33) delay for severe dehydration. Mothers of children with severe dehydration tended to be younger [median (interquartile range) 24 (21–28) vs. 27 (23–30) years, p = 0.07] and used less oral rehydration solution (63 vs. 80%, p = 0.08). Conclusion: Delay of >12 h in seeking healthcare for AD was not associated with severe dehydration.